An Expanded Role for HLA Genes: HLA-B Encodes a microRNA that Regulates IgA and Other Immune Response Transcripts - Chitnis, Nilesh; Clark, Peter M.; Kamoun, Malek; Stolle, Catherine; Brad Johnson, F.; Monos, Dimitri S. (Frontiers in Immunology, 2017)
We describe a novel functional role for the HLA-B locus, mediated by its intron-encoded miRNA, miR-6891-5p. We show that in vitro inhibition of miR-6891-5p impacts the expression of nearly 200 transcripts within the B-lymphoblastoid cell line (B-LCL) COX, affecting a large number of metabolic pathways, including various immune response networks. Amongst the top affected transcripts following miR-6891-5p inhibition are those encoding the heavy chain of IgA. We identified a conserved miR-6891-5p target site on the 3’UTR of both IGHA1 and IGHA2 transcripts, and demonstrated that this miRNA modulates the expression of IGHA1 and IGHA2. B-LCLs from IgA deficient patients expressed significantly elevated levels of miR-6891-5p as compared to unaffected family members. Upon inhibition of miR-6891-5p, IgA mRNA expression levels were increased and IgA secretion was restored in the B-LCL of an IgA deficient patient. These findings indicate that miR-6891-5p regulates IGHA1 and IGHA2 gene expression at the post-transcriptional level and suggest that increase in miR-6891-5p levels may contribute to the etiology of selective IgA deficiency.